PENGEMBANGAN PENDIDIKAN KARAKTER MELALUI KANTIN KEJUJURAN - Arrahim, Arrahim (Civic Education Department, Faculty of Teacher Training and Education, University of Muham, 2016)
The character of nations that now becomes the focus on various life aspects ishonesty. Now, the value of honesty is used as an example of a precious and costly thing. The weak value of honesty in school, like cheating and lying to a teacher, will negatively affect the education process and the learning outcome. The value of honesty can be improved through self-service canteen, so the material or main topic of the lesson in the subject can be immediately implemented. Self-service canteen is one of the effective strategies that enablethe students to learn and practice implementing the values of anti-corruption and as a forum for the education of the prospective anti-corruption national leader. The study conducted at SMA Negeri 8 Malang discussed (1) the implementation of character-building education development through the management of self-service canteen at SMA Negeri 8 Malang, (2) the description of the obstacles found in the implementation, (3) the description of solutionsto reduce the obstacles during the implementation. This study used a descriptive qualitative approach, in which the researcher was directly involved to find out information related to the title of the study. The data were collected through observation, interviews, and documentation. In addition, the informants were the headmaster, vice headmaster for student affairs, the coordinator of anti-corruption education/self-service canteen, civics teacher, and students ofSMA Negeri 8 Malang. Based on the research finding, the conclusion was obtained as follows: (1) Anti-corruption education/self-service canteen was launched 6 months ago. The concept was simple by providing snacks and beverages. The food was displayed on a table with is the price tag. There was a box for money from the box. The management mechanism was fully offered to the students, under the guidance of the management coordinator self-servicecanteen. (2) There was not any available change. Consequently, some students who owed forgot to pay. (3) The coordinator of self-service canteen gave instructions and guidance to the students continuously during the flag ceremony and the class activity, inserted the lesson materials about honesty, fairness, simplicity, struggle, and others.